Strategic planning indications from the point of view of the teaching staff of the Islamic University in Gaza - Salem Abdullah Halas (University of Science and Technology, Yemen, 2013)
Abstract                                                                                          The aim of the study is to find out the availability of strategic planning indications in the Islamic University in Gaza and its relationship to some variables. In other words, the study tried to answer the two following questions: • What is the level of availability of strategic planning indications in the Islamic University in Gaza? • Is there any statistical difference at α ≤ 0.05 in the level of availability of  strategic planning indications in the Islamic University in Gaza that can be attributed to the faculty, experience, and scientific rank of the teaching staff? The researcher selected a total number of 60 teaching staff of the Islamic University for the academic year 2011-2012. The tool of the study, the questionnaire, included 36 items that were divided into four categories which are: mission, values, strategic objectives and future vision of university education. Through related literature and data analysis, findings reveal that strategic planning indications in the Islamic University of Gaza are largely available from the point of view of the teaching staff.   The researcher recommends the following: • The Islamic University needs to enhance the strategic planning methodology; as strategic planning is the basis of development. • Working to utilize strategic planning methodology in the Islamic University in the field of values especially what is related to promoting an atmosphere of democracy at the university. • Working to utilize strategic planning methodology in the Islamic University in the field of future vision especially what is related to qualifying graduates to the job market. • Using strategic planning methodology in the Islamic University in the field of strategic planning  especially what is related to the importance of taking care and following up graduates. • Using strategic planning methodology in the Islamic University in the field of the university mission especially what is related to extra-curricular activities to help students make good use of their time.                                                                                                                                                                        Key words: strategic planning, mission, values, strategic objectives, future vision, the Islamic University